Income Inequality in Indonesia and Vietnam: The Role of Economic Growth, Inflation, Foreign Direct Investment - Nurlaela, Nurlaela; Sumaryoto Sumaryoto; Yolanda Yolanda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the effects of economic growth, inflation, foreign direct investment (FDI), and unemployment on income inequality and to examine how income inequality influences educational attainment in Indonesia and Vietnam. These two countries were selected because they share similar characteristics as developing economies in Southeast Asia, including rapid economic growth, increasing inflows of foreign investment, and ongoing structural economic transformation. Despite these similarities, both countries continue to face challenges related to unequal income distribution and disparities in access to quality education. This study adopts a quantitative research approach using secondary panel data collected over a specified period. Panel data regression analysis is employed to estimate the relationships among the variables and to identify the most significant determinants of income inequality and educational attainment. The findings are expected to provide empirical evidence on the extent to which macroeconomic factors contribute to income inequality and how inequality affects educational outcomes. By offering a comparative analysis of Indonesia and Vietnam, this research enriches the existing literature and provides policy recommendations for fostering inclusive economic growth, reducing income disparities, attracting productive investment, and improving human capital development through more equitable access to education.